The Relationship Between Adolescents' Knowledge of Reproductive Health and Premarital Sexual Behavior at the Adolescent Health Post - Purwanti, Rosa; Laila Faizah, Nur (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Adolescents are an age group vulnerable to environmental influences but often lack sufficient knowledge about reproductive health. This lack of understanding can trigger risky behaviors such as premarital sexual activity, which negatively impacts health and social aspects. Objective: The aim of this study is to examine the relationship between adolescents' knowledge level about reproductive health and premarital sexual behavior. Methods: This study employed an analytical observational design with a quantitative approach. The research used an analytical design with a cross-sectional approach. The study population consisted of all adolescents active, totaling 40 individuals, and all were included as samples using a total sampling technique. The research instrument consisted of a questionnaire on knowledge and premarital sexual behavior, with data analysis conducted using the Chi-Square test (α = 0.05). Results: showed that most adolescents have good knowledge (75%), sufficient knowledge (22.5%), and low knowledge (2.5%). Meanwhile, the majority of adolescent behavior is non-deviant (95%) and only 5% are deviant. The Chi-Square test results showed a p-value of 0.004 (p < 0.05). Conclusion: there is a significant relationship between the level of adolescent knowledge and premarital sexual behavior.